Pengaruh Motivasi Terhadap Kinerja Pegawai Di Kantor Kecamatan Sajoanging Kabupaten Wajo - Yuniarni Yuniarni; Muhammad Justiawal; Yuniarti Sari (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This study aims to reveal the effect of motivation on employee performance, especially in the Sajoanging District office, Kabupaten For this reason, information was collected by direct observation (observation), submitting questionnaires/questionsnaires and seeking supporting data in the form of official documents. The results showed that motivation had a positive and significant effect on employee performance in the Sajoanging District office, Wajo Regency. supported by the results of research which revealed that in a good category generally motivation is in the very good category and employee performance is in.